Binahong Leaves Water Extract (Anredera cordifolia (Tenore) Steen.) as a Natural Foaming and Antibacterial Agent of Antiseptic Liquid Bath Soap - Widiastuti Agustina Eko Setyowati; Reti Prabaraita Nurisah; Puput Istika Wulandari (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2020)
The research about the use of binahong leaves water extract (Anredera cordifolia (Tenore) Steen.) as a natural foaming and antibacterial agent in the production of antiseptic liquid bath soap has been conducted. The extraction of binahong leaves was done by the maceration method using water solvents, and then saponin identification was carried out using a foam test and Lieberman Burchard. Antiseptic liquid soap is made in 6 preparations with variations in the ratio of Sodium Lauryl Sulfate (SLS) and water extract of binahong leaves. Antibacterial activity test was carried out on Staphylococcus aureus and Escherichia coli using the excellent diffusion method. The results showed that binahong leaf water extract contained saponins and produced a stable foam of more than 10 minutes so that it could be used as a natural foaming agent in the production of antiseptic liquid bath soap. The soap produced meets the quality requirements of SNI 06-4085-1996 concerning Liquid Bath Soap, where preparation 4 has the best results with detergency power of 40%; pH 8,87; free alkali content of 0,04%; and a specific gravity of 1,06 gr/ml. A liquid bath soap with binahong leaves water extract surfactant (preparation 6) has the highest antibacterial activity against S. aureus and E. coli with inhibition area diameter of 13,5 mm (strong) and 12,5 mm (strong) respectively.